2011
DOI: 10.1080/09658416.2011.573856
|View full text |Cite
|
Sign up to set email alerts
|

Learning English as a foreign language in Taiwan: students’ experiences and beyond

Abstract: In Taiwan, earlier English instruction has become prevalent in response to the trend of English as an international language. Current studies are interested in investigating the outcomes or developmental process of learning English from a linguistic perspective. However, this article aims to reveal children's subjective experiences of learning English, examine implicit meanings of parents' attitudes towards earlier English instruction, and explore how children's experiences are shaped by the school context. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…The same suggestion was made by Wang (2008) to study how individual teachers have been implementing the English instruction on a local basis. Hsieh (2011) proposed a comparison of English learning by observing different instructional methods with young learners. Chen and Tsai (2012) found that the majority of research had been conducted on college and adult students, but suggested that research on primary and secondary school levels could result in a more unified framework on which to monitor and define English education in Taiwan.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The same suggestion was made by Wang (2008) to study how individual teachers have been implementing the English instruction on a local basis. Hsieh (2011) proposed a comparison of English learning by observing different instructional methods with young learners. Chen and Tsai (2012) found that the majority of research had been conducted on college and adult students, but suggested that research on primary and secondary school levels could result in a more unified framework on which to monitor and define English education in Taiwan.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In addition to those issues, some teachers mentioned demands from parents and administration (Hsieh, 2011). Lack of support and sufficient resources were cited additionally in regards to the school setting, along with the teachers questioning their own teaching abilities (Chiang, 2003;Her, 2007).…”
Section: Challenges For Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…The biggest problem of English teaching in Taiwanese preschool is the curriculum emphasizes too much on English and neglects the fundamental developmental tasks for children such as expressing their emotions through their mother tongue. This situation is mainly due to the parental held myth that 'learning English equals being international' (Hsieh, 2011;Liu, 2006). This is understandable of parents' expectation of international education in early years, but it so lacks clear focus and proper purposes in curriculum design.…”
Section: Curriculum and Global View Of Taiwanese Preschoolsmentioning
confidence: 99%
“…In this research, direct contact means the meeting of cultures but not English conversation. According to Hsieh (2011) andLiu (2006), many private preschools in Taiwan view English proficiency as an important part in foreign contact. In this study, with the assistance of translators to overcome the language obstacle, children could focus more on non-language contact such as listening, observing, and playing with people from other cultures.…”
Section: Foreign Experience Creating: Video Call First Strategy Is Tmentioning
confidence: 99%